A Hybrid Energy Harvester Based on Bowtie Periodic Antenna Surface - Mahmoud Abushab; Thamer S. Almoneef; Muhammad Amin; Omar F. Siddiqui (IEEE Access)
An innovative method is introduced for energy harvesting by combining a bowtie frequency selective rectenna surface with a traditional photovoltaic solar panel. The design of the rectenna antenna surface aims to optimize the geometry of the bowtie antennas for enhanced ambient RF energy absorption and rectification efficiency. Several integration techniques are explored to efficiently merge the RF and solar energy harvesting components into a unified system, considering factors such as spatial arrangement and DC electrical connections in both series and parallel. Tested efficiency analysis under various loads demonstrates the feasibility and effectiveness of the hybrid system as it captures the RF and solar energy and converts it into usable electrical energy. The RF-solar hybrid energy harvesting system can be employed in environment settings where energy sources exist intermittently.